Lack of awareness among contractor in project management: delay construction / Suria Yaacob - Yaacob, Suria (2006)
Nowadays, delays in completion are a common phenomenon and the projects costs are usually more than estimated. At the real-world application level, events never go as simply or easily as they appeared to on the drawing board and computer program. At the production stage, good project scheduling equates to how closely our planning of all tasks and activities of the project's development relates to the real-world application tasks involved in making it happen. Most construction contracts specify time for performance in achieving completion for the whole works and many have additional requirements for phased or sectional hand-over. Just as there are many misunderstandings on the purpose and principles of liquidate damage, there are many on extensions on time. It is common beliefs that liquidate damage provisions are solely for the benefit of the employer and extensions of time provisions solely for the benefit of the contractor. Both views are not only wrong but almost the reserve of true intentions.